Unpaid Overtime in Germany: Differences between East and West - Silke Anger (Schmollers Jahrbuch, 2005)
Although the standard work week is longer in East than in West Germany, there is a higher incidence and average amount of unpaid overtime worked in the new states. We try to explain the striking differences in unpaid overtime by analyzing the labor supply side. We focus on the investment character of overtime and examine whether workers use unpaid extra hours to signal higher productivity so as to reduce the risk of losing their job. Using panel data from the SOEP and approximating the risk of unemployment with regional unemployment rates we find partial evidence for the unemployment-overtime hypothesis.
Keywords: J22; D80; C23; 330; unpaid overtime; labor supply; signaling; unemployment; panel data; Arbeitszeit; Regionaler Arbeitsmarkt; Alte Bundesländer; Neue Bundesländer